Efek Penggunaan Ekstrak Tanaman Tegari (Dianella Sp) Terhadap Hewan Non Target (Ayam) - Rahmiyati Rahmiyati; Helda Orbani Rosa; Yusriadi Marsuni (www.ulm.ac.id, 2023)
Testing the effect of the extract of the plant Tegari (Dianella sp.) on non-target animals was carried out with the aim of knowing the dose that is effective in controlling rats but is still safe if consumed by nontarget animals. This research was conducted from March to April 2022 in Sawang Village, South Tapin Regency, South Kalimantan. The test used four doses, namely 120 grams/liter, 170 grams/liter, 220 grams/liter, and 270 grams/liter with four repetitions and three chickens in one repetition. The results of this study showed that there were still deaths with a percentage of 8.33% and the results of the ANOVA test showed that the effect of using the plant extract at the dose used did not significantly affect the mortality of chickens